Patterns and consequences of invasion of tropical montane forests by Cestrum aurantiacum Lindl. in the Western Ghats - Das, Arundhati A.; Ratnam, Jayashree; Jathanna, Devcharan (Frontiers in Ecology and Evolution, 2023)
In the montane forest-grassland mosaics of the Western Ghats, land cover conversion to silviculture and agriculture over the last five decades has resulted in both loss of natural habitats and widespread invasion of remnant habitat patches. While invasion of the grassland habitats of the mosaic has been relatively well studied, there have been few attempts to understand the extent to which forest habitats (locally known as sholas) have been affected by the spread of exotic species. Here we examine the patterns and impacts of invasion of shola forest understoreys by Cestrum aurantiacum Lindl., an exotic shrub species. At the landscape scale, we demonstrate that the presence and abundance of this invasive in shola understories is negatively related to distance from tea plantations. Further, the intensity of invasion is higher in areas with greater seasonality of temperature and lower mean annual precipitation. At the patch scale, invasion is greatest at shola edges and away from stream courses. We find that C. aurantiacum abundance has negatively affected the regeneration of native shola tree species as well as the abundance of native shola understorey shrubs. Our findings have important implications for the management and conservation of these mosaics.